(untitled) (Scientific Conference on Multidisciplinary Studies, 2025)
This thesis investigates the effectiveness of molecular diagnostic methods for the early detection of tuberculosis in the context of Uzbekistan. The polymerase chain reaction (PCR) and GeneXpert tests demonstrated higher accuracy and faster results compared to conventional methods, and allowed for the detection of rifampicin resistance. The findings confirm the need for the broader implementation of molecular diagnostics in national tuberculosis control strategies.